PHILOSOPHY OF INDEPENDENT CURRICULUM - Kafabihi, Chasbullah; Khaer, Abu; Ulum, Mohammad Bahrul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The Independent Curriculum is an initiative to reform the education system in Indonesia that aims to improve the quality of human resources through a philosophical and pragmatic approach. This article examines the curriculum from three main perspectives: ontology, epistemology, and axiology. In terms of ontology, the Independent Curriculum is designed to equip students with 21st-century competencies, such as critical, creative, and collaborative thinking, through project-based learning and strengthening the profile of Pancasila Students. The epistemological perspective includes the philosophical foundations of Progressivism, Constructivism, Humanism, and Anthropology that emphasize experiential learning and adjustment to students' needs. Meanwhile, axiology highlights the benefits of this curriculum as a tool to shape students' characters that are adaptive to changing times and global challenges. This study confirms that the implementation of the Independent Curriculum involves a flexible and thematic structure, allowing collaboration between subjects to create holistic learning. Thus, this curriculum not only prepares students academically but also forms moral, social, and personality values. The ultimate goal is to produce individuals who are independent, critical thinkers, and globally competitive, in accordance with the dimensions of Pancasila Students. This article recommends the importance of adaptive, innovative, and local values-based learning as a foundation for facing technological disruption and globalization.